Hierarchical, template-free self-assembly morphologies in CeO2 synthesized via urea-hydrothermal method. Issue 8 (1st June 2020) - Suarez Anzorena, Rosario; Muñoz, Fernando F.; Bonelli, Pablo; Cukierman, Ana Lea; Larrondo, Susana A.
Abstract: Nano-crystalline CeO2 was synthesized via the urea-hydrothermal method without templates or structure-directing agents. The synthesis parameters Ce 3+ to Ce 4+ and urea to cation molar ratios, reaction temperature and reaction time were varied to analyze their effect on morphology, texture and reducibility. The analysis of the obtained morphologies provides strong evidence of a hierarchical and sequential template-free self-assembly process that evolves from shuttles to dumbbells to spheres. In all cases, the morphology of samples remains unchanged even after calcination at 500 °C. The presence of Ce 4+ in the initial solution clearly provides the full self-assembly sequence and is decisive for obtaining non-hollow spheres of CeO2 with high specific surface area and high pore volume. Besides, if only Ce 3+ is present, typical CeOHCO3 shuttle-like particles with orthorhombic structure are obtained. The use of Ce 3+ in combination with Ce 4+ produces partial sequences of the self-assembly process that provide a strong indication of the hierarchical sequence. The urea to cation molar ratio controls the nucleation process and proves to be crucial to obtain the self-assembly sequence. On the other hand, temperature and reaction time show a moderate effect on morphology. Graphical abstract: Image 1